Artificial Intelligence in Islamic Family Law: Ethical Challenges and Maqāṣid al-Sharī‘ah Perspectives - Nuryamin Nuryamin; Yulia Fihtriany Rahmah; Muhammad Muhammad; Ai Imas Mursyidah Zein (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
The development of artificial intelligence (AI) systems has brought various opportunities as well as challenges in the field of law, including Islamic family law. This research aims to understand how AI systems work and are regulated in presenting the provisions of Islamic family law, as well as analyze their implementation in addressing emerging moral and ethical threats. In addition, this study assesses whether the use of AI in the Islamic family law system is in accordance with or contrary to the principles of maqashid asy-shari'ah. This study uses a qualitative method with a literature study approach. The analysis stages include data collection from secondary sources, data classification, and descriptive-analytical analysis. The results of the study show that the AI system in determining Islamic family law operates by managing data from various legal sources to form a draft answer that has legal certainty. However, there are ethical challenges, such as the potential for algorithm bias, the publication of personal data, automated law enforcement, and an over-reliance on AI. The analysis also shows that the application of AI has the potential to not fully meet the values of maqashid as-shari'ah. The novelty of this research lies in the systematic identification of the impact of the use of AI on compliance with the principle of maqashid as-shari'ah in Islamic family law. The implications of the study emphasize the need for special supervision of the quality of the laws produced by AI to remain in line with sharia principles.